Contrasting housing supply in Ireland, Northern Ireland and the rest of the United Kingdom - Wendy Disch; Paul Egan; Eoin Kenny; Kieran McQuinn (The Economic and Social Research Institute (ESRI), 2024)
This report examines the Irish, Northern Irish, Welsh, Scottish, and English residential markets with a particular focus on their capacity to increase housing supply over the short to medium term. Our approach compares and contrasts how differences across the housing markets, in key costs of production, the regulatory environment and economic dynamics, have impacted the supply of housing. The report suggests that across all housing markets, but particularly in the Irish case, the traditional financial sector does not appear to be able to provide the requisite amount of credit for the level of housing activity which has been deemed necessary to meet the underlying structural demand for housing. With this in mind, increased Government investment in the form of expanding the level of social and affordable stock of housing available emerges as a key finding across all markets.
Keywords: 330; Wohnungsmarkt; Wohnungsbestand; Soziale Wohnungspolitik; England; Irland; Nordirland; Schottland; Wales